2018
DOI: 10.1007/s00590-018-2199-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival and functional outcome of high tibial osteotomy for medial knee osteoarthritis: a 10–20-year cohort study

Abstract: The medium- to long-term survival and functional outcome after HTO was good to excellent at 10-20 years of follow-up. Age, gender, surgeon and surgical technique were identified as independent predictors of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 21 publications
2
50
0
4
Order By: Relevance
“…RTS has been investigated for HTO þ OCA independently, with data on OCA being most comparable with that for our cohort, as studies reporting isolated HTO have older populations and indications of diffuse medial compartment arthritis instead of a focal chondral defect. 3,27,44,45 Nielsen et al 38 reported a 75.2% rate of RTS after isolated OCA of the knee, and McCarthy et al 36 reported a 77% rate of RTS in young, competitive athletes, which are similar to the rate reported in the present study. A meta-analysis and a systematic review have both reported overall rates of RTS after OCA of 88%.…”
Section: Discussionsupporting
confidence: 88%
“…RTS has been investigated for HTO þ OCA independently, with data on OCA being most comparable with that for our cohort, as studies reporting isolated HTO have older populations and indications of diffuse medial compartment arthritis instead of a focal chondral defect. 3,27,44,45 Nielsen et al 38 reported a 75.2% rate of RTS after isolated OCA of the knee, and McCarthy et al 36 reported a 77% rate of RTS in young, competitive athletes, which are similar to the rate reported in the present study. A meta-analysis and a systematic review have both reported overall rates of RTS after OCA of 88%.…”
Section: Discussionsupporting
confidence: 88%
“…The operation principle of HTO is to transfer the pressure load in unicompartment by adjusting the force line of the lower extremities so as to relieve pain, restore knee joint function, and prolong knee joint life [ 5 ]. Numerous studies have shown that HTO has been proven to be a reliable treatment with good short- and medium-term efficacy for KOA after years of clinical practice [ 6 8 ]. In recent years, a growing number of orthopedic surgeons have shown great interest in HTO surgery due to a substantial increase in the number of patients with KOA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The survival of UKA is secondary to that of total knee arthroplasties (TKA) with a recent meta-analysis reporting 15-year survival of 76% and 93%, respectively (Evans et al 2019). The long-term survival of HTO seems inferior to both UKA and TKA with a declining survival from 75% at 10 years to 55% at 15 years (van Wulfften Palthe et al 2018). When UKA or HTO fail, conversion to TKA is a common solution (Lee et al 2019).…”
mentioning
confidence: 99%